Effect of Crop Specific Enriched Vermicompost on the Growth and Yield of Wheat and Pearl Millet: Enriched Vermicompost Effects on Wheat and Pearl Millet - Bhargava, Anjali; Pandey, Ankit; Sharma, S K; Jat, Ram Swroop; Yadav, Shankar Lal (Journal of Cereal Research, 2025)
The aim of this research was to investigate the effect of crop specific enriched vermicompost on the growth and yield of wheat and pearl millet. The experiment was laid out in Randomized Block Design with 3 treatments and were replicated three times The study was conducted on wheat and Pearl millet sown in soil with Enriched vermicompost (EVC) in treatment T1 50% EVC + 50% ,T2 RDF through chemical fertilizer and also 100% RDF T3 through Chemical Fertilizers. results showed that Effect of enriched vermicompost on the growth and yield parameters viz. plant height, number of tillers, leaf area index, ear heads plant-1,protein content, root length density at harvest (cm cm-3), shoot dry weight plant-1 (g), shoot fresh weight plant-1 (g), test weight (g) ,grain yield, Straw yield, Biological yield and harvest Index of wheat and pearl millet were found at par in case of 100% EVC, 50% EVC + 50% RDF and T3 : 100% RDF. The findings of this study suggest that crop specific enriched vermicompost can partially substitute the inorganic fertilizers up to 100 percent wheat and millet crops cultivated in central plateau and hill region zone of India. without hampering the crop yields.